Numerical and analytical methods with MATLAB for electrical engineers - Bober, William, 1930-; Stevens, Andrew, 1964- (CRC Press, 2013)
"The advantage of using the MATLAB software program over other packages is that it contains built-in functions that numerically solve systems of linear equations, systems of ordinary differential equations, roots of transcendental equations, integrals, statistical problems, optimization problems, signal processing problems and many other types of problems encountered in engineering. A student version of the MATLAB program is available at a reasonable cost. However, to students, these built-in functions are essentially black boxes. By combining a textbook on MATLAB with basic numerical and analytical analysis, (although I'm sure that MATLAB uses more sophisticated numerical techniques than are described in these textbooks), the mystery of what these black boxes might contain is somewhat alleviated. The text contains many sample MATLAB programs that should provide guidance to the student on completing the assigned projects"--Vydavatelská anotace
Keywords: numerické metody; numerická analýza; matematická analýza; MATLAB (software); matematický software; zpracování dat; výpočetní metody; matematické výpočty; elektrotechnika; numerical methods; numerical analysis; mathematical analysis; MATLAB; mathematical software; data processing; computational methods; mathematical calculations; electric engineering; monografie; monographs